OBSERVATION OF THE COLLAPSE AND FRACTIONAL REVIVAL OF A RYDBERG WAVEPACKET IN ATOMIC RUBIDIUM - Meacher, D; Meyler, P; Hughes, I; Ewart, P (1991)
The authors have excited and detected a radially localized electronic wavepacket in atomic rubidium. The wavepacket is formed of an optically induced coherent superposition of Rydberg states with mean principal quantum number, n=62. The motion of the wavepacket on a classical trajectory is monitored in a time-delayed ionization experiment. The collapse and revival of the classical dynamics is observed. During the period of nonclassical behaviour they observe, for the first time, a partial revival of the wavepacket. © 1991 IOP Publishing Ltd.